2022
DOI: 10.1259/dmfr.20210499
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surface- and voxel-based registration on the mandibular ramus for long-term three-dimensional assessment of condylar remodelling following orthognathic surgery

Abstract: Objectives: The purpose of the present study was to validate and compare the accuracy and reliability of surface- and voxel-based registration on the mandibular rami for long-term three-dimensional (3D) evaluation of condylar remodelling following Orthognathic Surgery. Methods: The mandible was 3D reconstructed from a pair of superimposed pre- and postoperative (two years) cone-beam computerized tomography scans and divided into the condyle, and 21 ramal regions. The accuracy of surface- and voxel-based regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The pre- and postoperative mandibles were semi-automatically segmented according to Holte et al [ 20 ]. Subsequently, the segmentation of the mandibular condyle was refined and registration was automatically performed to align the right and left pre- and postoperative rami, separately, as proposed in the protocol validated by Verhelst et al [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pre- and postoperative mandibles were semi-automatically segmented according to Holte et al [ 20 ]. Subsequently, the segmentation of the mandibular condyle was refined and registration was automatically performed to align the right and left pre- and postoperative rami, separately, as proposed in the protocol validated by Verhelst et al [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alignment by VBR, validated with the anterior cranial base as a reference, shows high accuracy [ 19 ], and is considered to be more consistent than SBR [ 12 , 19 ]. However, a recent study by Holte et al [ 20 ], validated and compared VBR and SBR on the mandibular rami for long-term 3D evaluation of condylar remodeling following orthognathic surgery. In this particular case, SBR was found to be more accurate and more reliable than VBR, possibly due to the influence of mandibular ramal remodeling [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although VBR has been shown to be more consistent and efficient than SBR, the differences between the two methods were statistically insignificant [ 52 , 53 , 54 ]. Another comparative study proved that SBR was more accurate and reliable than VBR on the mandibular ramus for the long-term 3D assessment of condylar remodeling following orthognathic surgery [ 55 ]. However, it was concluded that the performance difference might have been caused by the application of an inappropriate reference structure proposed in the literature [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another comparative study proved that SBR was more accurate and reliable than VBR on the mandibular ramus for the long-term 3D assessment of condylar remodeling following orthognathic surgery [ 55 ]. However, it was concluded that the performance difference might have been caused by the application of an inappropriate reference structure proposed in the literature [ 55 , 56 ]. Hence, according to the literature, no statistically significant or clinically relevant differences have yet been shown in the performance of the two methods.…”
Section: Discussionmentioning
confidence: 99%